Hard yet tough nc-CrAlN/a-SiNx nanocomposite coatings - Wang, Yuxi (2013)
In the past decades, hard or even super-hard ceramic coatings have been vigorously developed to satisfy the various requirements of practical applications in the machining industry. It is increasingly recognized that the enhanced hardness must be complemented by a proper toughness to avoid the catastrophic fracture when the coatings are subjected to an intensive contact force as in harsh conditions. However, results of the recent researches indicate that the increasing toughness is usually accompanied with a large sacrifice of the hardness. In this project, the state-of-the-art nitride hard coatings (i.e. CrAlN) and their nanocomposite variants (i.e. nc-CrAlN/a-SiNx, nc-: nanocrystalline, a-: X-ray amorphous) are fabricated using magnetron sputtering. The effect of the negative bias voltage on the CrAlN and the role of the Si content on the nc-CrAlN/a-SiNx are studied. The obtained results show that the bias voltage and the Si content are essential factors in determining the coating’s microstructure, and thus the mechanical properties. A proper bias voltage is beneficial for achieving a simultaneous improvement of the hardness and toughness since a dense microstructure and higher compressive stress are ready to be obtained. However, the increasing Si content leads only to a drop of toughness although a significant increase of hardness. To overcome the brittleness of the nc-CrAlN/a-SiNx nanocomposite, the distribution of the doped Si is varied and the influence of the distribution behavior is investigated. With the homogeneous and heterogeneous grading of Si, the toughness of brittle nc-CrAlN/a-SiNx is restored but still at an expense of hardness to different extents. Heterogeneous grading is more effective due to the laminated structure. It is believed that the inner layer with less Si provides the good toughness and adhesion while the outer layer with more Si offers the great resistance to the plastic deformation. On the other hand, a conventional toughening method by adding the ductile phase Ni is also evaluated. The obtained results indicate that with proper concentration of Ni (4.3 at.%), the toughness of the nc-CrAlN/a-SiNx nanocomposite is improved by 200% at an expense of 18% hardness drop. Based on the analyses of the above monolayers, a new routine in achieving hard-yet-tough ceramic coatings is proposed. A multilayers consisting of soft-tough CrAlN and hard-brittle nc-CrAlN/a-SiNx is fabricated. The dependence of the microstructure and mechanical properties on the bilayer thickness is revealed. Detailed studies on the microstructure indicate that the mixture of nanograins with different crystallographic orientations, the complex atomic configuration at the layer interface and the reduced grain size governed by the bilayer thickness are beneficial to achieve the enhanced toughness and high hardness. At bilayer thickness of 20 nm, the optimum toughness of the multilayers is improved by 5 times as compared to the nc-CrAlN/a-SiNx monolayer. Moreover, the hardness of multilayers also increases, and thus the achievable hard-yet-tough ceramic coatings.